The Scots may be brave but they are neither healthy nor happy - David N.F. Bell; David G. Blanchflower (Institute for the Study of Labor (IZA), 2005)
On almost all measures of physical health, Scots fare worse than residents of any other region of the UK and often worse than the rest of Europe. Deaths from chronic liver disease and lung cancer are particularly prevalent in Scotland. The self-assessed wellbeing of Scots is lower than that of the English or Welsh, even after taking into account any differences in characteristics. Scots also suffer from higher levels of self-assessed depression or phobia, accidental death and suicide than those in other parts of Great Britain. This result is particularly driven by outcomes in Strathclyde and is consistent with the high scores for other measures of social deprivation in this area. On average, indicators of social capital in Scotland are no worse than in England or Wales. Detailed analysis within Scotland, however, shows that social capital indicators for the Strathclyde area are relatively low. We argue that these problems need to be directly targeted as they seem unlikely to be fixed by more indirect policies aimed at raising economic growth.
Keywords: J4; 330; wellbeing; happiness; suicide; depression; Lebensqualität; Soziale Lage; Gesundheit; Selbstmord; Vergleich; Europa; Schottland; Großbritannien